Lefitolimod in Combination with Ipilimumab in Patients with Advanced Solid Tumors: A Phase I Trial - Mirella Nardo; Mohamed A. Gouda; Matthew J. Reilley; Amadeo B. Biter; Joann Lim; Stacie A. Bean; Ly M. Nguyen; Priya R. Bhosale; Casey R. Ager; Coline A. Couillault; Sarina A. Piha-Paul; Siqing Fu; et al. (Journal of Immunotherapy and Precision Oncology)
Introduction TLR9 agonists are immunomodulators that have been of interest for combined use with cancer immunotherapy. TLR9 agonists, such as lefitolimod (MGN1703), significantly increased Th1 response in preclinical models and have demonstrated efficacy in early clinical trials. This trial assessed the safety and preliminary efficacy of the combination of lefitolimod and ipilimumab in patients with advanced solid tumors. Methods This was a single-center, open-label, investigator-initiated phase I trial conducted at The University of Texas MD Anderson Cancer Center. Patients received leftolimod either subcutaneously (at escalating doses of 15–120 mg) or intratumorally (at the maximum feasible dose) in combination with ipilimumab (3 mg/kg). Paired biopsy samples were collected before the start of treatment and after two treatment cycles and analyzed by flow cytometry. Results We enrolled a total of 28 patients in this study with a median age of 56 years (range 19–75) in the escalation cohort and 60 years (range 34 –92) in the expansion cohort. The median number of prior lines of therapy was 4 (range 0–12). Eleven patients had at least one treatment-related adverse event (TRAE). The most common TRAEs were skin rash (n = 4, 14%), fatigue (n = 3, 11%), and pruritis (n = 2, 7%). No grade 4 or 5 AEs occurred, and no patients required dose reduction or treatment discontinuation due to AEs. The maximum tolerated dose (MTD) was not reached in this study. Of 28 patients, 21 patients had response-evaluable disease. No patients had a complete or partial response; 8 and 13 patients had stable and progressive disease as the best response, respectively. Paired biopsy samples were obtained from five patients. Increases in intratumoral CD8 T-cell frequency, memory CD8 phenotype (CD45RO+), and proliferation (Ki67+) in four of five patients suggested that the combination of lefitolimod and ipilimumab led to proinflammatory immune conditioning of the tumor microenvironment. Conclusions The combination of lefitolimod (administered subcutaneously or intratumorally) and ipilimumab was safe and well tolerated but demonstrated modest antitumor activity in patients with advanced cancers. ClinicalTrials.gov ID: NCT02668770